2017
DOI: 10.1111/jac.12205
|View full text |Cite
|
Sign up to set email alerts
|

On the use of spectral reflectance indices to assess agro‐morphological traits of wheat plants grown under simulated saline field conditions

Abstract: Successful breeding of plants for salinity stress tolerance requires realistic growing conditions and fast, non-destructive evaluation techniques for phenotypic traits associated with salinity tolerance. In this study, we used subsurface water retention technique (SWRT) as a growing condition and spectral measurements as an evaluation method to assess different agro-morphological traits of salt-tolerant (Sakha 93) and salt-sensitive (Sakha 61) wheat genotypes under three salinity levels (control, 60, and 120 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…There are few studies have investigated the performance of spectral reflectance indices (SRIs) for detecting the variations of these parameters under realistic saline field conditions. El-Hendawy et al [25] and Hackl et al [37] reported that, in salinity studies, the growth platform may impact on the use of spectral measurements to assess the phenotypic parameters and in the exploration of the importance of high-throughput phenotyping technique for evaluating salinity tolerance. Hackl et al [36] found that the relationships between SRIs and phenotypic parameters under simulated close-to-field conditions were more robust compared with the results of pot-grown plants conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are few studies have investigated the performance of spectral reflectance indices (SRIs) for detecting the variations of these parameters under realistic saline field conditions. El-Hendawy et al [25] and Hackl et al [37] reported that, in salinity studies, the growth platform may impact on the use of spectral measurements to assess the phenotypic parameters and in the exploration of the importance of high-throughput phenotyping technique for evaluating salinity tolerance. Hackl et al [36] found that the relationships between SRIs and phenotypic parameters under simulated close-to-field conditions were more robust compared with the results of pot-grown plants conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Salt-tolerant (Sakha 93) and salt-sensitive (Sakha 61) spring wheat cultivars [25,27] were used in this study. The two cultivars were grown during the 2016/2017 and 2017/2018 growing seasons at the Dierab Research Station of the College of Food and Agriculture Sciences, King Saud University, Saudi Arabia (24 • 25 N, 46 • 34 E; elevation 400 m).…”
Section: Plant Materials Experimental Site and Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperspectral reflectance sensing technique has been demonstrated to be a valuable and powerful alternative to traditional methods for the simultaneous indirect assessment of hundreds of morphophysiological parameters in a rapid, non-destructive, and consistent manner under different abiotic stresses [ 1 , 19 24 ]. Such technique is based on the capabilities of plants to reflect and absorb the light or solar radiation at the visible-infrared (VIS, 400–700 nm) the near-infrared (NIR, 700–1300 nm) and the shortwave-infrared (SWIR, 1300–2500 nm) wavelengths depending on biophysical and biochemical characteristics of the canopy, which are sensitive to water deficit stress.…”
Section: Introductionmentioning
confidence: 99%